Squamous cell lung carcinoma in a cat - Silva, José E.S. [UNESP] (2012)
Primary lung neoplasms are rare in small animals and present variable clinical signs. Here we report a case of a 4-year-old male cat which presented with apathy, dyspnea and pleural effusion. The cytological analysis of the pleural effusion revealed massive presence of atypical cells and the histopathological examination of the lung demonstrated tissue infiltration by atypical cells arranged in solid nests. The cytological and histopathological findings were compatible with squamous cell lung carcinoma.